2023
DOI: 10.3389/feart.2022.1039478
|View full text |Cite
|
Sign up to set email alerts
|

Research on cemented artificial pillars to replace protective inter-block coal pillars and stope failure laws

Abstract: Replacing protective inter-block coal pillars (PICPs) with cemented artificial pillars is proposed here to address low coal recovery rates. The use of cemented artificial pillars also reduces resource waste when PICPs are used in the short-wall block mining (SBM) process. A coal mine test area in northern Shaanxi, China, was employed as the study site. Artificial pillar replacement techniques were developed based on the layout characteristics of a typical SBM workface. High-strength cemented backfill materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…After many tests, the CPB ratio was determined to be OPC : FA + RS : CG: water, which is 1 : 4 : 2 : 1.2 [26]. The solid mass concentration was maintained at 85%, which met the requirements of coal mine backfill with a slump greater than 150 mm [27][28][29]. The test was divided into four groups according to the proportion of FA to the total mass of FA and RS: 0%, 20%, 40%, and 60%.…”
Section: Test Materialsmentioning
confidence: 99%
“…After many tests, the CPB ratio was determined to be OPC : FA + RS : CG: water, which is 1 : 4 : 2 : 1.2 [26]. The solid mass concentration was maintained at 85%, which met the requirements of coal mine backfill with a slump greater than 150 mm [27][28][29]. The test was divided into four groups according to the proportion of FA to the total mass of FA and RS: 0%, 20%, 40%, and 60%.…”
Section: Test Materialsmentioning
confidence: 99%
“…In the study on the degradation law of cemented artificial pillars as a replacement for protective inter-block coal pillars, Chi et al(2023) employed the Flac3D model to simulate real conditions in a mine in Shanxi, China. The results demonstrated that with a pillar width of 14m, the cemented artificial pillars could sufficiently bear the load requirements, and the surrounding rock mass remained relatively stable.…”
Section: Introductionmentioning
confidence: 99%